2021
DOI: 10.1016/j.biopsych.2020.12.015
|View full text |Cite
|
Sign up to set email alerts
|

High Blood Pressure and Risk of Dementia: A Two-Sample Mendelian Randomization Study in the UK Biobank

Abstract: BACKGROUND: Findings from randomized controlled trials have yielded conflicting results on the association between blood pressure (BP) and dementia traits. We tested the hypothesis that a causal relationship exists between systolic BP (SBP) and/or diastolic BP (DBP) and risk of Alzheimer's disease (AD). METHODS: We performed a generalized summary Mendelian randomization (GSMR) analysis using summary statistics of a genome-wide association study meta-analysis of 299,024 individuals of SBP or DBP as exposure var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 39 publications
(58 reference statements)
2
32
0
Order By: Relevance
“…First, although the study design was prospective and longitudinal, there were no interventions, so it is difficult to completely exclude reverse causations. As described in the Introduction, some studies suggest that low BP is a symptom (not a cause) of pre-clinical dementia [4], while a Mendelian randomization study suggested a causal effect of lower BP on dementia risk [5]. The neurological processes of Alzheimer's disease start 20 years before onset [49], and disentangling causes from outcomes over this period is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, although the study design was prospective and longitudinal, there were no interventions, so it is difficult to completely exclude reverse causations. As described in the Introduction, some studies suggest that low BP is a symptom (not a cause) of pre-clinical dementia [4], while a Mendelian randomization study suggested a causal effect of lower BP on dementia risk [5]. The neurological processes of Alzheimer's disease start 20 years before onset [49], and disentangling causes from outcomes over this period is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that low BP is a pre-clinical symptom rather than a cause of dementia [4]. However, a recent Mendelian randomization study reported that high blood pressure is causally linked to a lower risk of dementia [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we used the GWAS datasets from the exposure (serum calcium) and the outcome (AD) to estimate the effect of exposure on outcome ( He et al, 2020 ). MR analysis has three assumptions, which have been widely described ( Liu et al, 2018 ; Anderson et al, 2020 ; He et al, 2020 ; Wang L. et al, 2020 ; Zhang et al, 2020 ; Ou et al, 2021 ; Sproviero et al, 2021 ). Ethical approvals were provided in the original articles ( Lambert et al, 2013 ; Young et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…AD cases were autopsy-confirmed or clinically confirmed using the NINCDS-ADRDA criteria or DSM-IV guidelines ( Kunkle et al, 2019 ). The IGAP AD GWAS summary statistics have been widely used in recent MR analysis ( Liu et al, 2018 ; Anderson et al, 2020 ; He et al, 2020 ; Wang L. et al, 2020 ; Zhang et al, 2020 ; Ou et al, 2021 ; Sproviero et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…There were three primary MR studies each for type 2 diabetes [16][17][18] and LDL cholesterol [19][20][21] ; two studies each for HDL cholesterol 19,22 , total cholesterol 19,23 , triglycerides 19,21 , and systolic blood pressure 20,24 ; and one study each for diastolic blood pressure 25 , BMI 26 and circulating glucose 27 (Figure 1). The MR studies for diastolic blood pressure, BMI, and circulating glucose reported an overall estimate produced through the meta-analysis of two or more outcome cohorts.…”
Section: Identification Of Primary Mr Studiesmentioning
confidence: 99%